Analysis of the Influence of Digital Promotion and Physical Accessibility on Economic Sustainability of Tourism in Sambori Village - Ratnah; Ibrahim ali (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study is intended to empirically examine the impact of digital promotion and physical accessibility on the sustainability of the tourism economy in Sambori Village, Lambitu District, Bima Regency. This study highlights how limited road infrastructure, lack of public transportation, and lack of coordination of digital strategies hinder the optimization of the natural and cultural potential of villages to strengthen the local community's economy. Method: The study applied a quantitative approach with a causal associative design to uncover the causal relationship between the variables of digital promotion, physical accessibility, and tourism economic sustainability. Data collection was carried out through a Likert scale-based questionnaire that captured respondents' perceptions of physical access conditions, the effectiveness of digital promotions, and its application to tourism economic activities. Data analysis uses multiple linear regression to show the significance of the model and the magnitude of the influence of each independent variable. Result: The findings of the study indicate that the regression model with two predictor variables showed very strong predictive power, with values R = 0.889 and R² = 0.790 at a significance level of p < 0.001. Partially, physical accessibility was the most dominant predictor of tourism economic sustainability (β = 0.584; p < 0.001), which underscores the crucial importance of road infrastructure, transportation, and supporting facilities. Digital promotion also has a significant impact, albeit with a lower magnitude (β = 0.353; p = 0.002), especially in expanding the exposure and attractiveness of tourist destinations. Contribution: This research contains conceptual and empirical insights for rural tourism development through the affirmation of integration, increasing physical accessibility and strengthening digital promotion. The results show that infrastructure development is a key foundation in driving the tourism economy, while promoting digital functions as a catalyst for destination visibility and competitiveness. Therefore, this research provides an empirical basis for developing competitive, inclusive, sustainable tourism development strategies and policies, and focuses on improving the welfare of local communities in Sambori Village.